Toughness-dependent net-section resistance and ductility behaviour of high-strength structural steels S700 to S960 ... - Meissner, Mirco; Bartsch, Helen; Feldmann, Markus (RWTH Aachen University, 2024)
NORDIC STEEL 2024 : the 15th Nordic Steel Construction Conference, June 26-28, 2024, Luleå, Sweden 15. Nordic Steel Construction Conference, Nordic Steel 2024, Luleå, Sweden, 26 Jun 2024 - 28 Jun 2024; [Stockholm] : The Swedish Institute of Steel Construction 1-10 (2024). doi:10.5281/ZENODO.12508072 ... : Published by The Swedish Institute of Steel Construction, [Stockholm] ...